HEP14-activated PKC-ERK1/2 pathway boosts HEP14-empowered hADSCs for ovarian regeneration and functional restoration - Jiajia Sun; Qin Zhong; Kan Liu; Qili Sun; Chunan Lu; Yingtong Di; Lin Bai; Helen Picton; Bin Tang; Xiaojiang Hao; Liming Gui (Communications Biology)
Abstract Premature ovarian insufficiency (POI) and age-related natural-aging ovarian insufficiency (ARNA-OI) pose pressing global health challenges, necessitating effective therapeutic strategies and a deep understanding of their underlying mechanisms. This study investigates how HEP14, a PKC pathway activator, boosts the regenerative potential of human adipose-derived stem cells (hADSCs) for ovarian regeneration. Transcriptome analysis reveals that HEP14 modulates gene expression profile in hADSCs, enhancing their regenerative capacity. In mouse models of POI and ARNA-OI, co-administration of HEP14-empowered hADSCs (h-hADSCs) with HEP14/PLGA microspheres significantly improves ovarian regeneration and function. These effects are attributed to increased h-hADSC retention and transdifferentiation, enhanced antifibrotic and proangiogenic capability, along with an optimized dosing strategy. The upregulation of MMP1, PDGFD, and STC1 through the HEP14-activated PKC-ERK1/2 signaling pathway is crucial for these effects. Our findings highlight the pivotal role of h-hADSCs and the HEP14-activated PKC-ERK1/2 pathway in ovarian regeneration and provide a promising advancement in treating ovarian insufficiency.